Effects of a perpetrator’s physical attractiveness, socioeconomic status and gender on behaviour perception of the participants of sexual harassment situations - Petrauskaitė, Gabija; Čunichina, Ksenija (Psichologija, 2019)
Sexual harassment is still a widespread problem in today’s modern society. Therefore, it is important to identify extralegal factors that shape society’s attitudes towards sexual harassment cases and why, sometimes, the victim of sexual harassment is being blamed for the situation. Most of the previous studies do not explore the causal relationship between the characteristics of the accused and the attitudes towards the cases. Moreover, the results of many existing studies are contradictory. Therefore, the aim of this study is to determine the impact of sex, physical attractiveness and socioeconomic status (SES) of the perpetrator on the attitudes towards sexual harassment situations. A hundred seventy-nine respondents participated in the study. During the research, a fictional news report and situation assessment scale were used. It was found that only a perpetrator’s physical attractiveness and socioeconomic status had a statistically significant impact on the appraisal of the perpetrator and victim’s behavior in the situation. The physical attractiveness of the perpetrator resulted in a statistically significant positive appraisal of his behavior and a more negative appraisal of the victim’s behavior. SES only had a statistically significant impact on the appraisal of perpetrator’s behavior: when the perpetrator was of high SES, his behavior in a sexual harassment situation was perceived more negatively than that of low SES. Results of this research not only emphasize the importance of extralegal factors on the attitudes toward the sexual harassment victims and perpetrators among younger adults, but also indicates possible societal changes – diminished gender and opposite SES effects on the attitudes toward the aforementioned situations.